CXCR6+CD4+ T cells promote mortality during Trypanosoma brucei infection. - Gongguan Liu (Public Library of Science (PLoS), 2021)
Liver macrophages internalize circulating bloodborne parasites. It remains poorly understood how this process affects the fate of the macrophages and T cell responses in the liver. Here, we report that infection by Trypanosoma brucei induced depletion of macrophages in the liver, leading to the repopulation of CXCL16-secreting intrahepatic macrophages, associated with substantial accumulation of CXCR6+CD4+ T cells in the liver. Interestingly, disruption of CXCR6 signaling did not affect control of the parasitemia, but significantly enhanced the survival of infected mice, associated with reduced inflammation and liver injury. Infected CXCR6 deficient mice displayed a reduced accumulation of CD4+ T cells in the liver; adoptive transfer experiments suggested that the reduction of CD4+ T cells in the liver was attributed to a cell intrinsic property of CXCR6 deficient CD4+ T cells. Importantly, infected CXCR6 deficient mice receiving wild-type CD4+ T cells survived significantly shorter than those receiving CXCR6 deficient CD4+ T cells, demonstrating that CXCR6+CD4+ T cells promote the mortality. We conclude that infection of T. brucei leads to depletion and repopulation of liver macrophages, associated with a substantial influx of CXCR6+CD4+ T cells that mediates mortality.